Testing the hierarchical order of reading skills: a multifacetedrasch approach - Abu Kassim, Noor Lide; Jusoh, Zailani; Ismail, Nor Zatul-Iffa; Badrasawi, Kamal J I (IIUM Press, 2024)
The growing interest in new methods of assessing learning shows a dynamic progression towards a better understanding of the way assessment influences how teachers teach and how students learn. However, despite greater awareness of the importance of precise and rigorous assessment, many practitioners are still uninformed of the importance of psychometric or test theories which underlie the essential qualities of educational and psychological assessment, and the fundamental role they play in ensuring accurate and fair measurement. Without a thorough understanding of the principles of measurement and the use of defensible psychometric or test theories, even the best assessment methods cannot provide accurate and useful information about student learning, progress, and attainment. This introductory book was written with the hope to provide those involved in assessment and psychometric testing, a better understanding of psychometric theories, objective measurement, essential psychometric properties of cognitive tests and other psychological measurement instruments, errors in rater-mediated assessment, methods and issues in standard setting, and their impact on fair and equitable assessment and measurement.